The Influence of CSR on Company Financial Performance - Mahmud, M. Riza; Sari, Chindy Manika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The relationship between Corporate Social Responsibility (CSR) and corporate financial performance is a complex and multifaceted issue. While there is still some debate about the extent to which CSR actually impacts financial performance, a growing body of research suggests that it can lead to significant benefits for companies. This research aims to provide a comprehensive understanding of the relationship between CSR and corporate financial performance by examining the theoretical and empirical literature, identifying the potential mechanisms by which CSR can influence financial performance, and examining the factors that may moderate the relationship. The findings of this research can be of interest to a wide range of stakeholders and can contribute to the ongoing debate about the value of CSR.